Signs of Life: Affect, Language and (Extra)Humanness - Downey, Adrian; Sagy, Gonen (Journal of the Canadian Association for Curriculum Studies, 2022)
Fragmented and aiming toward provocation rather than elucidation, this article shares excerpts from the ongoing conversation between two scholars in education. The authors frame their conversation as response to the tensions raised by Monica Prendergast between the discourses of the ontological turn and the humanistically rooted field of poetic inquiry. Through engagement with posthumanisms, the affective turn, Indigenous refusal and Achille Mbembe’s writing on necropolitics, the authors suggest possible avenues of change for poetic inquiry given the tumultuous nature of the current moment. They conclude with the suggestion that resistance through language may be a necessary component of staying human amid the chaos of these times.